Appraisal of Neotectonic Activities in Shadi Kaur Catchment, Pasni, Balochistan-Pakistan - Waseem Khan; Mahnoor Mirwani; Inayat Ullah; Inayat Ullah; Aimal Khan Kasi; Shazia Fareed (International Journal of Economic and Environment Geology)
The goal of this research is to assess Neotectonic activity in the northern Pasni region of Balochistan-Pakistan. For a total of 57 drainage sub-basins, four geomorphic parameters were calculated. These include the Factor of asymmetry (FA), Shape of the Basin (SB), Hypsometric Integral (HI), and Length Gradient of the stream (LGS). The Index of Neotectonic(IN) was computed using a combination of the calculated geomorphic characteristics. The basins were then classified as having high, moderate, and low intensities as a result of this indexing. The tectonic strain by major lineation found between Hoshab fault and NNE trending Nai Rud fault and NNE trending Ghulaman-i-Bent fault, respectively, has influenced the mechanism of current channels geometry, according to the quantitative analysis. The INintensities distribution revealed considerable disparities amongst drainage sub basins, indicating variances in Neotectonic activity due to their placement in relation to the study area's fault networks. A total of8 knick pointsincluding the slope-break and vertical-step, were distinguished within the catchment area depending on the influencing factors.